Occurrence of Salmonella and presumptive Bacillus cereus in sesame products from Swiss retail stores - Karen Barmettler; Sara Boss; Michael Biggel; Roger Stephan (Italian Journal of Food Safety)
Sesame products such as tahini (tahin) or halva (halwa or helva), originating from Arabic cuisine, are becoming increasingly popular in Switzerland. Pathogens, such as Salmonella, can contaminate sesame products, as evidenced by various product recalls. In this study, the occurrence of Salmonella and Bacillus cereus group members was investigated in 100 sesame products (25 sesame seeds, 16 halva, 19 different sesame pastes, 7 sesame bars, 25 hummus, and 8 other products containing sesame) collected from Swiss retail stores. None of the products were positive for Salmonella, whereas B. cereus group members could be detected with bacterial counts between 1×102 and 9×102 CFU/g in 11 out of 100 (11%) products. The 11 isolates identified by matrix-assisted laser desorption ionization-time of flight were whole-genome sequenced with Illumina technology to confirm the identity of the pathogen, determine its toxin gene profile, and perform panC typing. Most of the isolates harbored genes encoding the enterotoxins Nhe, Hbl, and CytK. The isolates were assigned to diverse B. cereus group members, including one identified as B. cytotoxicus. In addition, one of the isolates matched genetically with the Thurigiensis strain used in biopesticide products. In conclusion, none of the investigated sesame products contained significant levels of Salmonella or B. cereus group members. However, as B. cereus with pathogenic potential was detected in multiple samples, proper storage is crucial to prevent its growth and ensure consumer safety, especially for products with high water activity such as hummus.